HEALTH INSURANCE OWNERSHIP TO INCREASE THE UTILIZATION OF PRIMARY HEALTH SERVICES IN RURAL HIGHLANDS - Yudi Adnan; Syahrul Basri; Munawir Amansyah; Zilfadillah Arranury (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2024)
Background: Access to adequate health services remains a global challenge, especially in rural and remote areas. Health insurance ownership has emerged as a solution to increase the utilization of health services.Objectives: This study aimed to explore the role of health insurance ownership in increasing the utilization of primary health services in rural highland areas in Indonesia.Methods: This research used a quantitative design with a cross-sectional survey method. The study population consisted of 728 adult individuals who were heads of households living in Kanreapia Village, Tinggi Moncong District, Gowa Regency, South Sulawesi. The sampling technique used purposive sampling. Data were collected through interviews with a structured questionnaire, including demographic variables, health insurance ownership status, and utilization of health services. Data analysis used descriptive statistics, chi-square tests, and logistic regression.Results: The results showed a significant relationship between demographic variables, health insurance ownership, and the utilization of health services. Individuals with health insurance were 6.764 times more likely to utilize health services compared to those without insurance (p<0.001).Conclusion: This study strengthens the evidence that health insurance ownership significantly increases an individual's likelihood of utilizing health services, especially in relatively isolated rural areas.